2020
DOI: 10.1097/meg.0000000000001819
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of endoscopic treatment for duodenal variceal bleeding: a systematic review

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…We previously performed a systematic review of all published evidence to evaluate the effectiveness and safety of endoscopic treatments for DV bleeding and found that the rates of rebleeding and mortality following endoscopic treatment for DV bleeding were 8.9% and 13.9%, respectively. [ 48 ] This discrepancy may be associated with the variable definition of “rebleeding” in the published literature and a publication bias in this systematic review. Overall, endoscopic treatment is an effective option for controlling EcV bleeding, but the long-term efficacy may be poor.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…We previously performed a systematic review of all published evidence to evaluate the effectiveness and safety of endoscopic treatments for DV bleeding and found that the rates of rebleeding and mortality following endoscopic treatment for DV bleeding were 8.9% and 13.9%, respectively. [ 48 ] This discrepancy may be associated with the variable definition of “rebleeding” in the published literature and a publication bias in this systematic review. Overall, endoscopic treatment is an effective option for controlling EcV bleeding, but the long-term efficacy may be poor.…”
Section: Discussionmentioning
confidence: 90%
“…However, the aforementioned a systematic review showed that endoscopic tissue adhesive injection may be preferable in the management of DV bleeding. [ 48 ] Given the small number of patients in our study, prospective controlled studies with large sample sizes are required to compare the efficacy and safety of different endoscopic treatments for EcV bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, no treatment strategies for duodenal varices have been established. Recently, Wan et al reported the safety, simplicity and rapidity of EIS for bleeding duodenal varices compared to surgical procedures and interventional radiology (8,9,26,27). Ineffectiveness or rebleeding can be expected in endoscopic variceal ligation for duodenal varices rupture (26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…The high rate of rebleeding (19.04%) in our study could be related to the severity of underlying liver disease as patients with advanced cirrhosis are more likely to present with rebleeds. 18…”
Section: Discussionmentioning
confidence: 99%
“…The high rate of rebleeding (19.04%) in our study could be related to the severity of underlying liver disease as patients with advanced cirrhosis are more likely to present with rebleeds. 18 Western data have shown that ectopic varices are more frequently noted in the duodenal bulb, while a Japanese study reported that the most common site of occurrence of DV was the descending duodenum. 4,19 In our own study, DVs were most common in the duodenal bulb and were seen in 21 patients, followed by second part of duodenum in 17 patients, while 3 patients had varices in the third part of duodenum.…”
Section: Esophageal Varices 13mentioning
confidence: 98%